2021
DOI: 10.2118/205029-pa
|View full text |Cite
|
Sign up to set email alerts
|

Subspace Ensemble Randomized Maximum Likelihood with Local Analysis for Time-Lapse-Seismic-Data Assimilation

Abstract: Summary Time-lapse-seismic-data assimilation has been drawing the reservoir-engineering community's attention over the past few years. One of the advantages of including this kind of data to improve the reservoir-flow models is that it provides complementary information compared with the wells' production data. Ensemble-based methods are some of the standard tools used to calibrate reservoir models using time-lapse seismic data. One of the drawbacks of assimilating time-lapse seismic data involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The non-adaptive localization scheme is the most adopted scheme for ensemble-based history matching, and many studies have demonstrated the benefit of using the nonadaptive localization scheme over the history matching without localization (Emerick and Reynolds, 2010;Sakov and Bertino, 2010;Oliver, 2013, 2017;Luo et al, 2017Luo and Bhakta, 2019;Silva Neto et al, 2021). However, there are limitations of using the non-adaptive localization scheme, as will be discussed later.…”
Section: Main Featuresmentioning
confidence: 99%
“…The non-adaptive localization scheme is the most adopted scheme for ensemble-based history matching, and many studies have demonstrated the benefit of using the nonadaptive localization scheme over the history matching without localization (Emerick and Reynolds, 2010;Sakov and Bertino, 2010;Oliver, 2013, 2017;Luo et al, 2017Luo and Bhakta, 2019;Silva Neto et al, 2021). However, there are limitations of using the non-adaptive localization scheme, as will be discussed later.…”
Section: Main Featuresmentioning
confidence: 99%
“…time-lapse seismic data, can result in over-fitting. There have been several efforts to balance the degrees of freedom of the problem and the information content in the data, including use of localization [8], reduction of data using machine learning techniques [9,10], reduction in data size using the correlation between the data and wells' cumulative production [11], sparse representation of data using a wavelet transform [12], assimilation of only the saturation front or transformation of the data into position of fluid fronts [13][14][15], combination of coarsening the data and coarse model simulations [16], and projection of data into ensemble subspace in combination with local analysis [17].…”
Section: Introductionmentioning
confidence: 99%